APPLICATION OF RIGHT TECHNOLOGY IN IMPROVING COMMUNITY INDEPENDENCE THROUGH LIFE SKILL PROGRAMS (Case Study of Appropriate Technology for Utilizing Local Potential of Sente Bulbs in Karangsetra Village, Pandeglang District, Banten Province) - Rudhi Hendharli (IKIP Siliwangi Bandung, 2018)
The purpose of this study is 1. To describe the planning of appropriate technology application in the cente-based tuber processing food business as a local potential. 2. To describe the process of applying appropriate technology in a cente-based tuber processing food business as a local potential. 3. To describe the results of the application of appropriate technology in a cente-based tuber processing food business as a local potential. 4. To describe the follow-up to the application of appropriate technology in the cente-based tuber processing food business as a local potential.The methodology used in this study was to use descriptive qualitative methods using data collection of observation guidelines, interview guidelines, documentation and literature studies, with informants managing Melati PAUD and parents of Melati PAUD students. The results showed that the efforts of the management of Paud Melati in training the use of appropriate technology to improve independence through cente processing, learning citizens were able to realize the results of entrepreneurial life skills obtained through the learning of citizens towards the adoption of cente processing equipment technology, product diversification from senti bulbs, increased insight into efforts at independence in business and income.The conclusion in this study is proven to be able to increase the independence of trainees. Training participants are able to market themselves or through marketing services that are entrusted to PAUD Melati managers the results of entrepreneurial training. Based on the results of research and discussion that has been carried out in this study, the researchers provide some suggestions for institutions and Technical Resource Persons should conduct life training activities using appropriate technology more intensive and more optimal in facilitating learning as one of the activities to improve the independence of trainees. Keywords: Appropriate Technology, Independence, Life Skills Education.